Chapter Solidarietà e politiche sociali tra Costituzione e Unione europea - Pezzini, Barbara (Studi e saggi, 2022)
A recognition of the duties of solidarity in constitutional provisions necessarily starts from Article 2 of the Constitution, in which solidarity is solemnly affirmed and recognised as a fundamental constitutional legal principle. Solidarity is realised as the source of non-derogable duties, including the tax duty. The construction of the tax relationship is no longer the purely atomistic one of the qualification of the reciprocal positions of the state (tax sovereignty) and the taxpayer (subject of abstention claims), but becomes the construction of the (tax) system in which the burdens arising from the common interest are distributed among all members of the community. Such a systematic dimension of solidarity, which is the one found in the Italian Constitution, is challenged in the context of European integration. And, in any case, as many have observed, the EU lacks a solidaristic set-up that characterises it in terms even comparable to those of the Italian constitutional system and in any case such as to authorise a systematic construction of European solidarity. The criticism of the current set-up must be followed by a proposal, which could be centred on a truly European tax.